PROKRASTINASI AKADEMIK DAN PRESTASI BELAJAR PADA SISWA SMK - Putri Nindia Lestari; Octa Reni Setiawati; Vira Sandayanti (Program Studi Psikologi Universitas Malahayati, 2022)
ABSTRACT: ACADEMIC PROCRASTINATION AND LEARNING ACHIEVEMENT IN HIGH SCHOOL STUDENTS This study aims to determine the frequency distribution of academic procrastination and learning achievement and to find out whether there is a relationship between academic procrastination and learning achievement in vocational students. This study uses product moment correlation analysis to determine whether there is a relationship between the two variables, academic procrastination and learning achievement. The population in this students of SMK Negeri 8 Bandar Lampung. The sample of this study was 167 students. Sampling using accidental sampling. The data collection method uses an academic procrastination scale based on aspects of academic procrastination and uses report for learning achievement data. Students of SMK Negeri 8 Bandar Lampung have a category of academic procrastination and learning achievement in the medium category. The correlation coefficient is r = .229 (p > .05), so it can be concluded that the there is no relationship between academic procrastination and student achievement in high school students. This shows that there is no significant relationship between academic procrastination and learning achievement in hish school students. As for suggestions for further research that is interested in researching the relationship between academic procrastination and academic achievement, it is better to consider researching other factors of learning achievement apart from academic procrastination. Keywords: Learning Achievement, Academic Procrastination, Students Penelitian ini bertujuan untuk mengetahui distribusi frekuensi prokrastinasi akademik dan prestasi belajar serta mengetahui apakah ada hubungan antara prokrastinasi akademik dengan prestasi belajar pada siswa SMK. Penelitian ini menggunakan analisis kolerasi product moment untuk mengetahui apakah ada hubungan antar kedua variabel yaitu prokrastinasi akademik dengan prestasi belajar. Populasi dalam penelitian ini yaitu siswa/i SMK Negeri 8 Bandar Lampung. Sampel dari penelitian ini adalah 167 siswa. Teknik pengambilan sampel menggunakan accidental sampling. Metode pengambilan data menggunakan skala prokrastinasi akademik berdasarkan aspek-aspek prokrastinasi akademik dan menggunakan nilai rapor untuk data prestasi belajar. Siwa/i SMK Negeri 8 Bandar Lampung memiliki kataori prokrastinasi akademik dan prestasi belajar pada katagori sedang. Koefisien kolerasi diketahui r = .229 (p > .05) sehinggga disimpulkan bahwa tidak ada hubungan prokrastinasi akademik dengan prestasi belajar siswa SMK. Hal ini menjunjukan bahwa prokrastinasi akademik dengan prestasi belajar pada siswa SMK tidak ada hubungan yang signifikan. Adapun saran bagi penelitian selanjutnya yang tertarik untuk meneliti tentang hubungan prokrastinasi akademik terhadap prestasi belajar sebaiknya juga mempertimbangkan untuk meneliti faktor-faktor lain prestasi belajar selain prokrastinasi akademik Kata Kunci: Prestasi Belajar, Prokrastinasi Akademik, SMK